2016
DOI: 10.4172/2157-7560.1000321
|View full text |Cite
|
Sign up to set email alerts
|

Pilin Vaccination Stimulates Weak Antibody Responses and Provides No Protection in a C57Bl/6 Murine Model of Acute Clostridium difficile Infection

Abstract: Clostridium difficile is the leading cause of nosocomial infections in the United States, adding billions of dollars per year to health care costs. A vaccine targeted against the bacterium would be extremely beneficial in decreasing the morbidity and mortality caused by C. difficile-associated disease; a vaccine directed against a colonization factor would hinder the spread of the bacterium as well as prevent disease. Type IV pili (T4Ps) are extracellular appendages composed of protein monomers called pilins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Additionally, the protective efficacy of C. difficile spore proteins was also investigated (29). However, the general of these vaccination candidates failed to generate a satisfactory immunity (15,17,18,29,35). The protective efficiency of candidate vaccines designed with a single protein is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the protective efficacy of C. difficile spore proteins was also investigated (29). However, the general of these vaccination candidates failed to generate a satisfactory immunity (15,17,18,29,35). The protective efficiency of candidate vaccines designed with a single protein is limited.…”
Section: Discussionmentioning
confidence: 99%
“…(13) found that toxin-based vaccines have no effect on C. difficile colonization or spore spreading from the host to the environment but may lead to an increased number of asymptomatic carriers (13,14). Considering these limitations, several passive immunotherapies against CDI (15,16) targeting other pathogenic factors, such as flagellum, S-layer proteins (SLPs), Cell wall protein 84 (Cwp84), CD0873, Pilin, and spore proteins, have been taken into consideration. However, some of these vaccine candidates failed to induce a sufficient level of immunity and provided only partial protection against CDI-related death (15,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…87,88 For this reason, new passive immunotherapies that target different pathogenic factors, such as pilin, spore proteins, flagellum, and S-layer proteins, are being explored. [89][90][91]…”
Section: New Approachesmentioning
confidence: 99%
“…Toxin‐based vaccines do not prevent CD colonization and cannot restrain the spread of spores from the host to the environment, resulting in a possible increase of asymptomatic carriers 87,88 . For this reason, new passive immunotherapies that target different pathogenic factors, such as pilin, spore proteins, flagellum, and S‐layer proteins, are being explored 89–91 …”
Section: Treatmentmentioning
confidence: 99%
“…More recently these authors immunized mice with various pilins, whether combined or as individual proteins. Unfortunately, “low anti-pilin antibody titers and no protection upon C. difficile challenge were observed” ( Maldarelli et al, 2016 ).…”
Section: Vaccines Targeting C Difficile Surface Cmentioning
confidence: 99%